2001
DOI: 10.1046/j.1365-3148.2001.00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and motivations of Canadian autologous blood donors

Abstract: Preoperative autologous blood donation in Canada has increased in the last decade due to concerns about allogeneic blood safety. As economic policies necessitate the validation of autologous blood donation, it is important to assess potential changes. This study examines the motivations and perceptions of patients participating in a Canadian autologous blood donation programme. The study was conducted at the Ottawa Hospital, Civic Campus. Questionnaires were developed and then administered to 100 consecutive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Despite the advent of pre‐operative autologous donation (Moltzan et al ., 2001), in‐theatre blood recycling and the manufacture of blood components such as coagulation factors, in the UK, there is no foreseeable end to the dependence upon voluntary, anonymous blood donation. In the UK, blood donation has always been nonremunerated.…”
mentioning
confidence: 99%
“…Despite the advent of pre‐operative autologous donation (Moltzan et al ., 2001), in‐theatre blood recycling and the manufacture of blood components such as coagulation factors, in the UK, there is no foreseeable end to the dependence upon voluntary, anonymous blood donation. In the UK, blood donation has always been nonremunerated.…”
mentioning
confidence: 99%
“…This amount was lower than that reported previously (between $1100 and $1900 US) (Lee et al ., 1998a). However, a Canadian study found that 70% of respondents were prepared to pay up to $100 Canadian ($73 US) per unit of autologous blood (Moltzan et al ., 2001). This difference may be explained by a number of factors, such as the income level of participants in each study, the ability to pay and the various expectations regarding the costs of health care in Australia, Canada and the US.…”
Section: Discussionmentioning
confidence: 99%
“…During the early to mid 1980s when the risk of allogeneic blood transfusion-transmitted HIV was as high as 1:100 in some areas [5] and no test existed to detect its presence, interest in and demand for this life saving alternative increased. Studies have demonstrated that fear of contracting an infectious disease, particularly HIV, from allogeneic blood transfusion has been a primary motivating factor in the decision to donate autologous blood [4,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%